2021
DOI: 10.1007/s13760-021-01691-5
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination as a result of an immune response in patients with COVID-19

Abstract: The coronavirus disease of 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus-2 (SARS CoV-2), that already appeared as a global pandemic. Presentation of the disease often includes upper respiratory symptoms like dry cough, dyspnea, chest pain, and rhinorrhea that can develop to respiratory failure, needing intubation. Furthermore, the occurrence of acute and subacute neurological manifestations such as stroke, encephalitis, headache, and seizures are frequently stated in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 76 publications
(78 reference statements)
1
31
0
Order By: Relevance
“…Further, PASC (long COVID) often presents with similar neurological symptomatology to our two cases (Proal & VanElzakker, 2021;Shabani, 2021). Indeed, one small study of older adults hospitalised with COVID-19 found favourable outcomes when patients were administered combined vitamin D (1000 IU), magnesium (150 mg), and vitamin B12 (500 µg) (Tan et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Further, PASC (long COVID) often presents with similar neurological symptomatology to our two cases (Proal & VanElzakker, 2021;Shabani, 2021). Indeed, one small study of older adults hospitalised with COVID-19 found favourable outcomes when patients were administered combined vitamin D (1000 IU), magnesium (150 mg), and vitamin B12 (500 µg) (Tan et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…Myalgic Encephalomyelitis, chronic Lyme disease). Indeed, SARS-CoV-2 infection has been reported to cause neurological problems including demyelination (Zanin et al, 2020) via multiple mechanisms including host inflammatory response and autoimmunity (Shabani, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In other words the brain and spine Magnetic resonance imaging (MRI) of the patient exhibited a new onset of multiple, non-enhancing demyelinating lesions. It was assumed that following SARS-CoV-2 infection, the pro-inflammatory environment induced by the cytokine storm might be responsible for the activation of glial cells with subsequent demyelination as reported by ( Mehta et al, 2020 , Shabani, 2021 ). As a para-infective or post-infective phenomenon, the virus could trigger the activation of antibodies against the glial cells ( Zanin et al, 2020 ).…”
Section: Neurological and Neuropsychiatric Complicationsmentioning
confidence: 99%
“…COVID-19 infection caused by SARS-CoV-2 is now considered a risk factor of demyelination of the CNS, as well as the peripheral nervous system [125]. Several cases have already been presented for acute demyelination after COVID-19 infection [126][127][128][129].…”
Section: Sars-cov-2mentioning
confidence: 99%